E4 Butterfly Complexes (E=P, As) as Chelating Ligands. Issue 44 (2nd September 2015) - Schwarzmaier, Christoph; Heinl, Sebastian; Balázs, Gábor; Scheer, Manfred
Abstract: The coordination properties of new types of bidentate phosphane and arsane ligands with a narrow bite angle are reported. The reactions of [{Cp′′′Fe(CO)2 }2 (μ, η 1:1 ‐P4 )] (1 a ) with the copper salt [Cu(CH3 CN)4 ][BF4 ] leads, depending on the stoichiometry, to the formation of the spiro compound [{{Cp′′′Fe(CO)2 }2 (μ3, η 1:1:1:1 ‐P4 )}2 Cu] + [BF4 ] − (2 ) or the monoadduct [{Cp′′′Fe(CO)2 }2 (μ3, η 1:1:2 ‐P4 ){Cu(MeCN)}] + [BF4 ] − (3 ). Similarly, the arsane ligand [{Cp′′′Fe(CO)2 }2 (μ, η 1:1 ‐As4 )] (1 b ) reacts with [Cu(CH3 CN)4 ][BF4 ] to give [{{Cp′′′Fe(CO)2 }2 (μ3, η 1:1:1:1 ‐As4 )}2 Cu] + [BF4 ] − (5 ). Protonation of 1 a occurs at the "wing tip" phosphorus atoms, which is in line with the results of DFT calculations. The compounds are characterized by spectroscopic methods (heteronuclear NMR spectroscopy and IR spectrometry) and by single‐crystal X‐ray diffraction studies. Abstract : The butterfly has landed : The first examples of the coordination of E4 butterfly complexes (E=P, As) are presented. It is shown that the "wing‐tip" E atoms are capable of acting as ligands towards Cu + cations. The E4 moieties act as bidentate ligands with a very narrow bite‐angle, which is comparable to that of dppm (bis(diphenylphosphino)methane).